Peripartum Cerebral Angiopathy - Sallam, Amr; McWilliams, Sebastian R.; Boyle, Karl; Larkin, Caroline M. (Journal of Neuroanaesthesiology and Critical Care, 2023)
Peripartum cerebral angiopathy (PCA) is a rare cerebrovascular disorder of unclear etiology that typically occurs in the first postpartum week. The aim of this case series is to present seven cases of PCA and the associated outcomes. Two of the cases were typical of a reversible cerebral vasoconstriction syndrome (RCVS) and had no long-term sequelae. Five of the cases involved intraparenchymal hemorrhage in the absence of an underlying vascular lesion, with three of the five cases having associated cerebral vasoconstriction. None of the patients had a documented history of preeclampsia or hypertension during pregnancy. It has been suggested that there is pathophysiological overlap between PCA and eclampsia and RCVS. There is limited evidence in the literature in this regard and, in most cases, treatment has been supportive only. As a condition, PCA may be under-recognized in the neurocritical care setting. Increased awareness of this condition, its manifestations, and options for management may optimize outcomes.
Keywords: peripartum; postpartum angiopathy; reversible cerebral vasoconstriction syndrome; cerebral intraparenchymal hemorrhage